SARS-CoV-2 anti-RBD and anti-N protein responses are differentially regulated between mother-child pairs: insight from a national study cohort at the Faroe Islands - Jarlhelt, Ida; Hansen, Cecilie Bo; Pérez-Alós, Laura; Weihe, Pál; Petersen, Maria Skaalum; Garred, Peter (Frontiers in Immunology, 2024)
Knowledge about SARS-CoV-2 antibody dynamics in neonates and direct comparisons with maternal antibody responses are not well established. This study aimed to characterize and directly compare the maternal and infant antibody response in a national birth cohort from the Faroe Islands.The levels of immunoglobulins (Ig) targeting the receptor binding domain (RBD) of the spike protein and the nucleocapsid protein (N protein) of SARS-CoV-2 were investigated in maternal blood and umbilical cord blood from neonates. The study included 537 neonates and 565 mothers from the Faroe Islands, and follow-up samples were collected 12 months after birth. Multiple linear regression models were used to assess associations of maternal parameters with maternal and neonatal Ig levels and pregnancy outcomes.The finding showed that neonates acquired varying levels of SARS-CoV-2 antibodies through transplacental transfer, and the levels were significantly influenced by the mother's vaccination and infection status. The study also found that maternal vaccination and the presence of SARS-CoV-2 antibodies targeting spike RBD were associated with gestational age and APGAR scores. Furthermore, the anti-RBD and -N protein-specific antibody response dynamics during 12 months after birth exhibited differences between mothers and children. RBD and N protein responses were maintained at follow-up in the mother's cohort, while only the N protein response was maintained at follow-up in the children's cohort.In conclusion, SARS-CoV-2-specific immune responses in newborns rely on maternal immunity, while the persistence of SARS-CoV-2-specific Igs appears to be differently regulated between mothers and children.The study provides new insights into the dynamics of SARS-CoV-2-specific immune responses in newborns and underscores the nuanced relationship between maternal factors and neonatal humoral responses.